2014
DOI: 10.9790/3013-04060207011
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and phytochemical analysis of Calotropis gigantea root, latex extracts.

Abstract: The root and latex of Calotropis gigantea were screened for its antimicrobial and phytochemical activities. The solvents used for the roots and latex extraction were n-hexane, benzene, acetone, ethanol, aqueous. The extract was tested against infectious disease causing bacterial such as Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus using the well diffusion method. The aqueous, ethanolic and acetone extract of root of calotropis gigantea inhibition against all the test microbe ranging from 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…In a previous study, the extract showed a high concentration ranging from 0.25 to 0.5 mg/mL effective against B. cereus, B. subtilis, E. coli, K. pneumonia, M. luteus, S. aureus and S. typhi respectively. Methanol extract has value of MIC in range of 0.5 to 2.0 mg/mL (Seniya et al, 2011).The aqueous, ethanolic and acetonic extracts of root of C. gigantea impart sufficient inhibitory actions against the test microbe ranging from 10 mm to 16 mm diameter inhibitory zones (Kori and Alawa, 2014). Hence, compared to the earlier reports, a good inhibition was achieved in the present study.…”
Section: Antimicrobial Activity Of Root Extractsupporting
confidence: 54%
See 2 more Smart Citations
“…In a previous study, the extract showed a high concentration ranging from 0.25 to 0.5 mg/mL effective against B. cereus, B. subtilis, E. coli, K. pneumonia, M. luteus, S. aureus and S. typhi respectively. Methanol extract has value of MIC in range of 0.5 to 2.0 mg/mL (Seniya et al, 2011).The aqueous, ethanolic and acetonic extracts of root of C. gigantea impart sufficient inhibitory actions against the test microbe ranging from 10 mm to 16 mm diameter inhibitory zones (Kori and Alawa, 2014). Hence, compared to the earlier reports, a good inhibition was achieved in the present study.…”
Section: Antimicrobial Activity Of Root Extractsupporting
confidence: 54%
“…Maximum inhibition efficiency was observed against K. penumoniae at 500 µg/mL. The bacterial strains B. cereus and S. aureus were susceptible to plant extracts with zone of inhibition (≥20 mm) diameter respectively (Seniya et al, 2011) and out of the hexane and benzene extracts only limited inhibition was observe in benzene extract against the E. coli only (Kori and Alawa, 2014).…”
Section: Antimicrobial Activity Of Leaf Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of C. gigantea latex against toothache, caries, and chest colds [38], and that of the dried and burned stem against inflamed tonsils [36] is supported by the substantial inhibitory effects of aqueous and/or ethanolic extracts of the sap of the plant on the growth of various pathogenic bacteria as well as yeast species [87,88]. Aqueous, methanol, ethanol, and petroleum ether extracts of the leaves of the plant also exerted broad antimicrobial activity against cultured bacterial strains [88], clinical isolates of Candida species [89], and the plant-pathogenic The Contribution of Javanese Pharmacognosy to Suriname's Traditional Medicinal… DOI: http://dx.doi.org/10.5772/intechopen.97732 fungus Fusarium mangiferae that can cause serious damage to mango cultivations [90]. Additionally, a methanol extract from the rootbark and its petroleum ether, chloroform, and ethyl acetate fractions, as well as crude aqueous, ethanolic, and acetone extract also displayed broad in vitro antibacterial activity [89,91].…”
Section: Apocynaceae -Calotropis Gigantea (L) Dryandmentioning
confidence: 99%
“…Calotropis gigantea Linn is flowering plants belong to Asclepidaceae family. It is also known as Akada, Aak, Mandar, Aakh etc 3 .…”
Section: Introductionmentioning
confidence: 99%